Нові знахідки виробів прикладного мистецтва з «міста Володимира» - Мовчан, І.І.; Боровський, Я.Є.; Архіпова, Є.I. (Археологія, 1998)
У статті публікуються цікаві знахідки виробів прикладного мистецтва Х—ХІІІ ст., виконані візантійськими та київськими майстрами, знайдені на території «міста Володимира». В статье впервые публикуются находки уникальных произведений искусства, найденные на территории «города Владимира» в Киеве: фрагменты византийской амфоры IX—X в. с богатой врезной орнаментацией, а также изготовленные местными ремесленниками фигурка коня из комплекта костяных изобразительных шахмат XII—XIII в., половина костяной гирьки кистеня с княжеским знаком схемы Мстислава Великого и изделия из пирофиллитового сланца X—XI в.— медальон и пряслице, украшенные гравированной орнаментацией. It is the first publication of findings of unique applied art works discovered in the territory of the «city of Vladimir» in Kiev: fragments of the Byzantine amphora of the 9th-10th cent, with rich incised decoration, a figurine of a horse from a kit of ivory chess-men of the 12th-13th century, a half of a small ivory weight of a bludgeon with the prince’s symbol of Mstyslav the Great’s pattern, articles made of pyrophyllite schist dated 10th-11th centuries: a medallion and spindle ware decorated with engraved ornament.